2017
DOI: 10.18632/oncotarget.21224
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline treatment increases resistance to oxidative stress and extends lifespan in Drosophila via FOXO

Abstract: Minocycline is a semi-synthetic tetracycline derivative antibiotic that has received increasing attention for its non-antibiotic properties, mainly anti-inflammatory, tumor-suppressive, and neuroprotective effects. Drosophila is a widely used genetically tractable model organism for studying organismal aging by virtue of its short lifespan and ease of cultivation. In this study, we examined the effects of minocycline on Drosophila lifespan and its associated traits. Minocycline-supplemented food significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 35 publications
(43 reference statements)
1
14
0
Order By: Relevance
“…Minocycline displays PARP inhibitory activity with an IC 50 of 42 nM in humans 21 and is well tolerated in flies. 22 We fed flies with a range of concentrations from 0 to 1 mg/mL minocycline for 24 hr before stress and measured survival rates 96 hr after stress induction. Drug treatment of flies with ubiquitous knockdown of Parg revealed a dose-dependent partial rescue of the lethality ( Figure S4G).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Minocycline displays PARP inhibitory activity with an IC 50 of 42 nM in humans 21 and is well tolerated in flies. 22 We fed flies with a range of concentrations from 0 to 1 mg/mL minocycline for 24 hr before stress and measured survival rates 96 hr after stress induction. Drug treatment of flies with ubiquitous knockdown of Parg revealed a dose-dependent partial rescue of the lethality ( Figure S4G).…”
mentioning
confidence: 99%
“…Although we expect that the effect of minocycline on survival in this assay was due to its effect on PARP, we cannot exclude off-target or non-specific effects. 22 Given that PARP inhibitors are currently in trials for various types of cancer, it is possible that these drugs could be tested for clinical effectiveness in this orphan disease, where they could have a positive effect. Potentially clinically relevant PARP inhibitors include (1) minocycline, an FDA-approved tetracycline derivative that displays PARP inhibitory activity; (2) dihydroisoquinoline (DPQ), a non-FDA-approved potent PARP-1 inhibitor used in experimental research; and (3) veliparib (ABT: 888), a potent PARP-1 and PARP-2 inhibitor currently in clinical trials for the treatment of various type of cancers (IC 50 ¼ 42, 37, and 4.4 nM, respectively).…”
mentioning
confidence: 99%
“…Increasing evidence indicates that the dFOXO gene function is closely to lifespan in flies. For instance, the dFOXO overexpression decreased mortality and increased lifespan of flies via reducing oxidative stress, and the dFOXO is required both for transcriptional changes that mark the fly's dietary history and for nutritional programming of lifespan by excess dietary sugar (Blice-Baum et al, 2015;Dobson et al, 2017;Lee et al, 2017;Liu et al, 2012). In addition, endurance exercise can delay heart aging by activating dFOXO/SOD pathway (Wen et al, 2019).…”
Section: P<0mentioning
confidence: 99%
“…Several antibiotics, including minocycline and macrolides, present with both antimicrobial and anti-inflammatory properties as they de-escalate NLRP3 (Pradhan et al, 2016). Recent studies have shown that minocycline also presents with senolytic properties as aside from inhibiting NLRP3, it facilitates senescent cell removal (Labro, 2002; Li J. et al, 2016; Lee et al, 2017).…”
Section: Beta Amyloid: Friend or Foe?mentioning
confidence: 99%